2012
DOI: 10.1038/aja.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in sperm aneuploidy levels in severe oligoasthenoteratospermic patients after medical therapy: a preliminary report

Abstract: The objective of this study was to investigate whether medical therapy can reduce sperm aneuploidy levels and improve the results of intracytoplasmic sperm injection (ICSI) in patients with severe idiopathic oligoasthenoteratospermia (OAT). Thirty-three infertile couples requiring ICSI because of severe idiopathic OAT after at least one unsuccessful ICSI cycle were considered. Semen parameters (concentration, motility and morphology), the percentage of aneuploid sperm and the results of ICSI (the number of ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Cavallini et al (2012), in their study, reported that 22 out of 33 male patients with severe idiopathic oligoasthenoteratozoospermia (OAT) of infertile couples whose partners had undergone at least one ICSI cycle, showed reduced sperm aneuploidy levels (assessed using fluorescent in situ hybridization performed on chromosomes X, Y, 13, 15, 16, 17, 18, 21 and 22) and improved sperm morphology after 3 months of treatment with LC 2 × 1 g/day, ALC 2 × 500 mg/day and cinnoxicam (a lipophilic NSAID) 1 × 30 mg/every 4 days [ 89 ]. Men with OAT have been reported to have elevated prostaglandin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Cavallini et al (2012), in their study, reported that 22 out of 33 male patients with severe idiopathic oligoasthenoteratozoospermia (OAT) of infertile couples whose partners had undergone at least one ICSI cycle, showed reduced sperm aneuploidy levels (assessed using fluorescent in situ hybridization performed on chromosomes X, Y, 13, 15, 16, 17, 18, 21 and 22) and improved sperm morphology after 3 months of treatment with LC 2 × 1 g/day, ALC 2 × 500 mg/day and cinnoxicam (a lipophilic NSAID) 1 × 30 mg/every 4 days [ 89 ]. Men with OAT have been reported to have elevated prostaglandin levels.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of ICSI pregnancies and live births in severe idiopathic OAT patients improved with a course of L-carnitine, acetyl-L-carnitine, and cinnoxicam. The improvement occurred in the patients who had their sperm aneuploidy reduced and their sperm morphology increased [ 24 ]. Further varicocele correction presents a possible method to optimize a couples' reproductive potential increasing ICSI offspring or decreasing the need for complex assisted reproductive technology [ 25 ].…”
Section: Specific Indications To Improve Spermatogenesis Before Artmentioning
confidence: 94%
“…Cavallini et al . () reported reduced sperm aneuploidy, improved sperm quality and improved clinical outcomes in oligo‐astheno‐teratospermic patients who were treated with L‐carnitine, acetyl‐L carnitine and cinnoxicam. Young et al .…”
Section: Therapeutic Approachesmentioning
confidence: 98%